A COMPARISON OF THE EFFECTS OF BALANCE– PROPRIOCEPTION AND AEROBIC EXERCISES ON FUNCTIONAL STATUS, PAIN, AND BALANCE IN PATIENTS WITH FIBROMYALGIA SYNDROME - A RANDOMIZED CONTROLLED STUDY - Hadi Yavuz; Türker Şahinkaya; Musa Doruk; Mert Zure; Şensu Dinçer; Ayşegül Ketenci; Gökhan Metin (İstanbul Tıp Fakültesi Dergisi)
Objective: Difficulty in performing daily activities and loss of balance are common complaints in addition to generalized pain in fibromyalgia syndrome (FMS) patients. Exercise is an effective treatment for fibromyalgia. There are a variety of forms of exercise used to treat fibromyalgia. This study aimed to compare the effects of aerobic and balance-proprioception exercises on pain, functional status, and balance in female patients with fibromyalgia.Material and Method: Female patients with fibromyalgia syndrome who applied to the university physical medicine and rehabilitation department clinic were evaluated for eligibility. Patients were allocated into two groups: the aerobic exercise group and balance-proprioception group. These two groups exercised under the supervision of a physiotherapist three days a week for a total of 6 weeks. Visual Analogue Scale (VAS) was used for pain severity, Fibromyalgia Impact Questionnaire (FIQ) was used for functional status assessment, and balance-stabilidisty system (Biodex Balance System) was used for balance status assessment. Each measurement was repeated twice, before and after the treatment, and the results were compared.Result: Fifty-one patients were enrolled including 26 patients in the aerobic exercise group and 25 patients in the balance-proprioception group. Both aerobic exercise and balance proprioception exercise groups showed significant improvement following the treatment in FIQ ((34.63±11.85, 29.60±12.77, respectively, p<0.001) and VAS (4.54±1.83; 4.28±1.92, respectively, p<0.001), all Eyes-Closed Mediolateral Stability Index (EC-MLSI) (0.41±0.43, 0.35±0.19, respectively, p=0.39), Eyes Closed Overall Stability Index (EC-OSI) (0.85±0.53; 0.80±0.33, respectively, p<0,001), Eyes Closed Anteroposterior (EC-APSI) Stability Index (0.65±0.32, 0.62±0.29, respectively, p<0.001) and Eyes-Opened Mediolateral Stability (EO-MLSI) (0.15±0.07, 0.14±0.05, respectively, p=0.019). Similar to before-treatment findings, there was no statistically significant difference between groups in the FIQ, VAS, and balance scores after treatment (p>0.05).Conclusion: Both aerobic exercise and balance-proprioception exercises are effective methods in improving pain, functional status, and balance abilities of patients with FMS. In addition to aerobic exercise programs that are often prescribed nowadays, programs consisting of balance–proprioception exercises can also be a preferable option in FMS treatment.